Spatial relationships between the standing vegetation and the soil seed bank in a fire-prone encroached dehesa in Central Spain - Torres, Ivan; Cespedes, Blanca; Perez, Beatriz; Moreno, Jose M (PLANT ECOLOGY, 2013)
Postfire vegetation regeneration in many fire-prone ecosystems is soil seed bank dependent. Although vegetation and seed bank may be spatially structured, the role of prefire vegetation patterns and fire in determining postfire vegetation patterns is poorly known. Here, we investigated the spatial patterning of species abundance and richness in the vegetation and seed bank of a Mediterranean encroached dehesa in Central Spain. The seed bank was studied with and without a heat shock simulating a spatially homogeneous fire. Semivariograms and cross-semivariograms showed that species richness in the vegetation was aggregated in patches, mainly of herbs, with highest values corresponding to high herb cover and low tree cover. Species richness in the seed bank was also structured in patches, but the spatial pattern was weak. Seedling density of germinates in the seed bank also showed weak spatial pattern. Heating increased overall germination and species richness, and the intensity of the spatial pattern of species richness, particularly of herbaceous species. However, seed bank density patterns disappeared after heat shock because of increased germination of shrubs without spatial pattern. Our results document that the spatial structure of plant richness in the vegetation may persist after fire due to the spatial patterns of herbaceous species in the seed bank, and that postfire species richness patterns can arise independently of fire intensity patterns. However, the spatial structure of the vegetation after fire can be altered by the feedback between shrub encroachment and an eventual fire because of the ubiquitous germination of shrubs.
Keywords: Land abandonment; Land-use change; Seeder; Semivariogram; Species richness

Spatial relationships between the standing vegetation and the soil seed bank in a fire-prone encroached dehesa in Central Spain - Torres, Ivan; Cespedes, Blanca; Perez, Beatriz; Moreno, Jose M. (PLANT ECOLOGY, 2013)
Postfire vegetation regeneration in many fire-prone ecosystems is soil seed bank dependent. Although vegetation and seed bank may be spatially structured, the role of prefire vegetation patterns and fire in determining postfire vegetation patterns is poorly known. Here, we investigated the spatial patterning of species abundance and richness in the vegetation and seed bank of a Mediterranean encroached dehesa in Central Spain. The seed bank was studied with and without a heat shock simulating a spatially homogeneous fire. Semivariograms and cross-semivariograms showed that species richness in the vegetation was aggregated in patches, mainly of herbs, with highest values corresponding to high herb cover and low tree cover. Species richness in the seed bank was also structured in patches, but the spatial pattern was weak. Seedling density of germinates in the seed bank also showed weak spatial pattern. Heating increased overall germination and species richness, and the intensity of the spatial pattern of species richness, particularly of herbaceous species. However, seed bank density patterns disappeared after heat shock because of increased germination of shrubs without spatial pattern. Our results document that the spatial structure of plant richness in the vegetation may persist after fire due to the spatial patterns of herbaceous species in the seed bank, and that postfire species richness patterns can arise independently of fire intensity patterns. However, the spatial structure of the vegetation after fire can be altered by the feedback between shrub encroachment and an eventual fire because of the ubiquitous germination of shrubs.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Land abandonment; Land-use change; Seeder; Semivariogram; Species richness

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Patterns of seedling recruitment in West-Mediterranean Quercus ilex forest influenced by canopy development - Espelta, Josep Maria; Riba, Miquel; Javier, Retana (Journal of Vegetation Science, 1995)
Abstract. Quercus ilex (holm oak) coppice forests belong to the most representative communities in the western part of the Iberian Peninsula. Due to the high sprouting potential of holm oak after coppicing, the dynamics of recruitment of new individuals in existing populations has been largely overlooked. In these forests, the density of seedlings increases in old stands, as a result of the remarkable increase in the recruitment of 1-yr and 2-yr old seedlings, probably due to better environmental conditions for germination. Older seedlings show a tendency towards increasing survival under some degree of canopy closure, since their density appears to be higher just before complete canopy closure takes place. Nevertheless, the reduced growth of seedlings in older stands due to low light levels causes age distributions of holm oak seedlings to change drastically, with saplings older than 15 yr becoming very unusual in these stands. Therefore, a bottleneck of recruitment appears at this sapling stage and prevents vigorous regeneration just before thinning. Present conditions of genet density and management tend to prevent population renewal. Dynamics of the seedling bank reinforce the role of gap formation through small or large scale perturbations in population turnover.
Keywords: Holm oak; Regeneration; Seeder; Seedling dynamics; Sprouter; thinning